Estimation of productivity and adaptivity of potato varieties of different ripening groups under conditions of Arkhangelsk region - L. A. Popova; L. N. Golovina; A. A. Shamanin; V. M. Maslova (Аграрная наука Евро-Северо-Востока, 2017)
Article presents results of complex estimation of potato varieties bred in leading institutions of Russia and Belarus under conditions of north territories of Arkhangelsk region by the main economic valuable parameters that allow to reveal varieties non-zoning in Arkhangelsk region but obtained high productivity and diseases resistance. Varieties were studied on durability of phonological stages; productivity; defeat with diseases; content of starch and dry matter in tubers. Adaptive potential of varieties was estimated for each group of ripening that could give high productivity at annual change of weather conditions of Arkhangelsk region. During investigation, next varieties with high plasticity and productivity were selected: early varieties - Meteor, Zhukovsky ranniy, Lyubava, Kholmogorsky; middle-early varieties - Sudarynya, Lileya, Fritella, Favorit; middle varieties - Tuleevsky, Skarb; middle-late varieties - Zhuravinka. Highest productivity had early variety Meteor - 59.8 t/ha with marketability 93.4%; middle-early variety Sudarynya - 47.2 t/ha, marketability 80.4%; middle variety Tuleevsky - 53.1 t/ha, marketability 86.6%; middle-late variety Zhuravinka - 37.6 t/ha, marketability 78.5%. Visual estimation of plants testifies rather high resistance of varieties against diseases. More that half of varieties (69%) have shown low or very low lesion with phytophtoroses. Next varieties were defeated with virus X: Ocharovanie - 9%, Sudarynya, Kolobok, Lileya, Manifest - 3%; with virus M - varieties Sirenevyj Tuman, Ocharovanie, Ognivo, Sudarynya, Volat, Skarb - from 3 up to 9%; with virus S - varieties Sirenevyj Tuman, Ocharovanie, Uladar, Briz - from 3 up to 9%. Variety Lomonosovsky was selected within early varieties by content of starch and dry matter - 12 and 17.8%; within middle-early - variety Fritella -14.7 and 20.4%; within middle varieties - variety Nadezhda - 14.4 and 20.1%; within middle-late one - variety Zol'sky - 13 and 18.8% respectively.